Urethral bulking agents for female stress urinary incontinence. Issue 3 (22nd February 2019) - Hussain, Sadiya M.; Bray, Rhiannon
Abstract : Urethral bulking agents (UBAs) to treat stress urinary incontinence was first described in the 1930s, when paraffin was used to increase urethral resistance. Since then, several agents have been introduced to the market, with varying degrees of safety, efficacy, and durability. The agents currently available include calcium hydroxyl apatite (Coaptite®), carbon coated zirconium (Durasphere®); polydimethylsiloxane elastomer (Macroplastique®); and polyacrylamide hydrogel (Bulkamid®). The latest product, PDMS‐U (Urolastic ®) is a silicone gel that polymerizes when injected. The short term efficacy of UBAs are generally encouraging; however, longer follow up results show the success rates are reduced and many women will require a repeat treatment. This review looks at the currently available UBAs, application techniques, and the clinical data on their safety and efficacy.